2019
DOI: 10.3390/met9080886
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Phenomenon and Flow Field in Ladle of RH Process

Abstract: Particle image velocimetry (PIV) system was adopted to investigate the relationship between the mixing phenomenon and the flow field of a 210 t RH degasser by a 1:4 scale water model. The results of mixing simulation experiments indicated that the mixing time decreased with the increase of gas blowing rate. However, with the increase of Snorkel immersion depth (SID), the mixing time presented a decreasing rend firstly and then increased. The measurement of flow fields of RH ladle by PIV system can explain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Due to too much molten steel in the vacuum chamber and the expanding of the inactive layer in RH ladle however, the utilization rate of the gas driving force begins to decrease. Therefore, the mixing time starts to increase with the increase of SID [5].…”
Section: Refining the Steel In Ladlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to too much molten steel in the vacuum chamber and the expanding of the inactive layer in RH ladle however, the utilization rate of the gas driving force begins to decrease. Therefore, the mixing time starts to increase with the increase of SID [5].…”
Section: Refining the Steel In Ladlesmentioning
confidence: 99%
“…The papers covered by this Special Issue are state-of-the-art in the fields of crucial multiphase interactions in the steel making furnaces: basic oxygen furnace (BOF) [1] and electric arc furnace (EAF) [2]. Next, the research focuses on the matters related to the secondary refining processes; fluid's turbulences with nearby metal-slag interface in the ladles [3], the evolution of inclusions for Ti-bearing steels treated by calcium [4], and an influence of aluminum on flux flow in the ladle during Ruhrstahl Heraeus (RH) degassing operations [5]. Other papers are devoted to a geometry of impact area in the tundish [6], cleanliness consequences of an intermixing of the different steel grades in the tundish [7], and the reoxidation of steel from tundish cover flux [8].…”
Section: Contribution To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Except for the gas flow rate, Kishan et al [ 7 ] found that a deep snorkel immersion depth (SID) can produce a large circulation flow rate. The effect of the SID on mixing time was also investigated by Zhang et al [ 17 ] It was found that the mixing time first decreased with an increased immersion depth, while a reverse trend was found with a further increased immersion depth.…”
Section: Introductionmentioning
confidence: 98%